Health‐Related Quality of Life Associated With Pain Health States in Spinal Cord Stimulation for Chronic Neuropathic Pain. Issue 1 (17th September 2020) - Duarte, Rui V.; Soliday, Nicole; Leitner, Angela; Taylor, Rod S.
Abstract: Objectives: A substantial proportion of patients have recently reported pain reduction levels of ≥80% following treatment with Evoked Compound Action Potential (ECAP) spinal cord stimulation (SCS). The additional health‐related quality of life (HRQoL) utility gain that can be achieved in this patient group is unclear. The aim of this study is to quantify the HRQoL utility values seen in a remission health state (defined as ≥80% pain reduction) and contrast with more traditional health states of <50% and ≥50% pain relief. Materials and Methods: Pain intensity assessed using a 100 mm visual analogue scale (VAS) and EQ‐5D‐5L questionnaires were collected from 204 patients treated with ECAP SCS for chronic back and leg pain and followed up to 12 months. Utility values were derived using EQ‐5D‐5L responses crosswalked to EQ‐5D‐3L. Linear regression models adjusted for baseline utility values and patient demographics were used to compare differences in utility values across health states. Results: Patients in the remission health state (i.e., ≥80% pain reduction) consistently reported statistically significant greater utility values (+0.09 to +0.15, all p  < 0.003) compared to patients reporting ≥50% pain relief at 3‐ and 12‐month follow‐up for overall, back, and leg VAS pain. The gain in utility values per percent unit of pain reduction was statistically significant at 3‐ and 12‐month follow‐up with a mean increase in HRQoL utility score between 0.003 and 0.005 observed for each percent of pain reduction. Conclusion: Our analyses show that patients in a remission health state report statistically and clinically significant better HRQoL than patients experiencing lesser pain relief.